Dual beam half Radial Line Slot Array (RLSA) antennas - Purnamirza, Teddy; Akbar, Insanul; Mulyono; Sutoyo; Susanti, Rika; Mohd Ibrahim, Imran; Rahmi, Depriwana (Tylor & Francis, 2022)
Dual-beam half Radial Line Slot Array (RLSA) antennas were introduced for the first time in this article. Their uniqueness lies in the fact that only half model of RLSA antennas was used instead of full circle models to ensure they are applicable in small devices. Moreover, the slots were placed on the antenna’s background, which is unusual, to produce a beam on the backside. It is important to note that the half RLSA and the antenna background used to produce the beam affected the power flow orientation within the antennas’ cavity, thereby, causing a center frequency shift problem. This led to the proposal of a technique of frequency design shift to overcome this problem by designing and simulating 120 dual-beam half RLSA models after which the best model was fabricated and measured to verify the simulation. The results showed the possibility of designing dual-beam antennas with symmetrical beams having 10.1 dB gain, 30° and 150° directions, and 37° beamwidths. It was discovered that this gain is 3 dB lesser than the value for a single beam antenna and this is suitable based on the theory of beam splitting. Moreover, the antenna was also able to perform low reflection and quite broad bandwidth for Wi-Fi needs. The design of the antenna was further verified based on the similarity between the results of the measurement and simulation.